FORMULASI STRATEGI PT PACIFIC ROYALE AIRWAYS DALAM MEMASUKI INDUSTRI TRANSPORTASI UDARA DI INDONESIA - , Putu Mukunda Padma, Dr. Agus Setiawan, M.Soc.Sc. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
This thesis attempts to analyze the formulation strategy of Pacific Royale Airways to entered the airline industry in Indonesia. The purpose of analysis in this thesis is to identify the external and internal factors in airline industry to illustrate the characteristics of airline industry , and formulate appropriate strategies to enhance the competitiveness of Pacific Royale Airways to entering the airlinet industry in Indonesia. PEST analysis and Five Competitive Factors of Industry Competitiveness by Michael Porter (1979) is used to analyze the external factors, while for internal factorsis used Value Chain analysis. For the Pacific Royale Airwaysâs formulation strategy is used SWOT analysis. The data collection in this study are using the interview to the interal of Pacific Royale Airways and several experts in aviation industry. In addition it also conducted the questionnaires and secondary datasources that support this study. The results of the analysis in this thesis, explains that the stable political conditions and increased of GDP growth in Indonesia led the airline industry in Indonesia of 12.7% and also change the lifestyle in movement. Besides the results of the Five Forces Porter analysis are threat of new entrants and threat of substitute products is low, while the intensity of competition between the players, the bargaining power of suppliers and bargaining power of buyers is high. With outsourcing applied in supporting activities and doing service level agreement with the supplier of Pacific Royale Airways, the profit is expected to increase to 7%. While the results of the SWOT analysis as a tool of strategy formulation for Pacific Royale Airways is implementing strategies that support an aggressive strategy to increase the market share and the number of the aircraft that being used as a production tools and improve the service to customers.